2024
DOI: 10.1177/09544062241237666
|View full text |Cite
|
Sign up to set email alerts
|

Structural modeling and investigation of cantilever load-bearing mechanism in telescopic wing

Chunfeng Li,
Hong Xiao,
Hongwei Guo
et al.

Abstract: Telescopic wing requires changing the wingspan under aerodynamic load. Structural deformation caused by forces and moments will result in increased driving forces or even stagnation. Deformation and distributed contact force of linear motion pair of the load-bearing mechanism which considers the geometric nonlinearity of guide rail is necessary to predict the driving force, the mechanical efficiency, or the stiffness matching in the optimal design process. Aiming at the cantilever load-bearing mechanism, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…When entering the water, the wings retract through a telescopic device to reduce the impact during entry and the resistance when navigating underwater. The technology for wing retraction is currently quite mature, and Li [24] has conducted structural research on this technology, which can be applied to this new type of vehicle, as shown in Figure 5. This technology has already been widely patented, and Zhu [25] researched a new one, it is a patented achievement of a retractable variable wing.…”
Section: Description Of New Water-air Trans-media Uavmentioning
confidence: 99%
“…When entering the water, the wings retract through a telescopic device to reduce the impact during entry and the resistance when navigating underwater. The technology for wing retraction is currently quite mature, and Li [24] has conducted structural research on this technology, which can be applied to this new type of vehicle, as shown in Figure 5. This technology has already been widely patented, and Zhu [25] researched a new one, it is a patented achievement of a retractable variable wing.…”
Section: Description Of New Water-air Trans-media Uavmentioning
confidence: 99%